Structural evolution of Malay Basin, its link to sunda block tectonics - Mansor, M.Y. (Elsevier Ltd, 2014)
The Malay Basin is located offshore West Malaysia in the South China Sea, within north central region of 1st order Sunda Block. The basin developed partly as a result of tectonic collisions and strike-slip shear of the Southeast Asia continental slabs, as the Indian Plate collided into Eurasia, and subsequent extrusion of lithospheric blocks towards Indochina. The Sunda Block epicontinental earliest rift margins were manifested by the Palaeogene W-E rift valleys, which formed during NW-SE sinistral shear of the region. Later Eocene NW-SE dextral shear of (2nd order) Indochina Block against East Malaya Block rifted open a 3rd order Malay Basin. Developed within it is a series of 4th order N-S en-echelon ridges and grabens. The grabens and some ridges, sequentially, host W-E trending 5th order folds of later compressional episodes. The Malay Basin Ridge and Graben Model explains the multi-phased structural deformation which started with, the a) Pre-Rift Palaeo/Mesozoic crystalline/metamorphic Basement, b) Synrift phase during Paleogene, c) Fast Subsidence from Late Oligocene to Middle Miocene, d) Compressional inversion of first Sunda fold during Late Miocene, and e) Basin Sag during Plio-Pleistocene with mild compressional episodes. The subsequent Mio-Pliocene folding history of Malay Basin is connected to the collision of Sunda Block against subducting Indian-Australian Plate. This Neogene Sunda tectonics, to some degree after the cessation of South China Sea spreading, is due to the diachronous collision along the 1st order plate margins between SE Asia and Australia. Â© 2014.